Propuesta de la planificación de instalaciones y diseño de actividades en un centro de relajación y meditación en el cantón el triunfo - Chávez Navarrete, Karla Johanna (2010)
In The relaxation and meditation centers are products of the human need to escape a hectic lifestyle, which leads to problems of stress, meditation centers that are now very popular in the country, especially in cities such as Quito and Guayaquil by the pace of metropolitan life from them. El Triunfo, a tourist spot untapped, with primary and secondary forests so their flowers and animals in addition to its favorable climate plays a fundamental role and are ideal for meditation and relaxation activity. The habitants and the M.I. Municipality expressed their acceptance of this new proposal will have infrastructure such as: Hotels, restaurants, spa and yoga room facilities as well as ecological bridges, footpaths, landscaping and parking are also inculcated the sustainability of this ecosystem, and such studies were conducted such as FODA , carrying capacity in addition to environmental impacts, marketing strategies, marketing management and ultimately financial aspects which showed that the center is being restored and sustainably. All this to show that it is possible to live sustainably and simultaneously conjugate with relaxation, meditation and tourist activities